Transgressions in Kenyan, Christian, Queer: Response to the Roundtable - van Klinken, Adriaan (My University, 2022)
This article is a response to a Religious Studies Review roundtable discussion of my book, Kenyan, Christian, Queer: Religion, LGBT Activism, and Arts of Resistance in Africa (Penn State University Press, 2019). The roundtable contributions make me reflect on the ways in which Kenyan, Christian, Queer presents a methodological innovation in the study of religion. This innovation is captured, in good queer spirit, as a number of transgressions: of academic disciplines, of distance toward sources and research subjects, and of religion as the object of analysis.
Keywords: Religious Studies; Christian Studies (incl. Biblical Studies and Church; queer